DEMOGRAPHIC CHARACTERISTICS AND INDEPENDENT ACTIVITIES OF ELDERLY'S DAILY LIFE IN NURSING HOMES: A CROSS SECTIONAL STUDY - Putra, Kusuma Wijaya Ridi (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The independence of the elderly in carrying out their daily activities can show the ability of the elderly to fulfill their needs independently. There are several variables related to the independence of the elderly, both from internal and external of the elderly. Objectives: This study aimed to determine the relationship between age, gender, educational level, history of disease, independent activities of the elderly's daily life. Methods: This study used a correlational research design with a cross-sectional study approach. This research was conducted at UPT PMKS Mojopahit Mojokerto from March to April 2022. The target population in this study were all elderly people living in UPT PMKS Mojopahit Mojokerto. The sampling technique used by the researchers was purposive sampling technique, in order to obtain a total sample of 25 elderly people. This study used demographic data and the Katz independence index as instruments. The statistical test used in this study was the Pearson Product Moment Correlation Test. Results: Based on the research data, it was found that only age was related to the independent activities of the elderly's daily life (r = .578, p-value = .002). Conclusion: Age is the main variable that can affect the changes experienced by an elderly person, so that it can affect the ability of the elderly to carry out their daily activities.